2021
DOI: 10.3390/molecules26144313
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties of Hydrocarbon and Fluorocarbon Surfactants Ternary Mixture at the Water-Air Interface

Abstract: Measurements were made of the surface tension of the aqueous solutions of p-(1,1,3,3-tetramethylbutyl) phenoxypoly(ethylene glycols) having 10 oxyethylene groups in the molecule (Triton X-100, TX100) and cetyltrimethylammonium bromide (CTAB) with Zonyl FSN-100 (FC6EO14, FC1) as well as with Zonyl FSO-100 (FC5EO10, FC2) ternary mixtures. The obtained results were compared to those provided by the Fainerman and Miller equation and to the values of the solution surface tension calculated, based on the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The results of the morphological analysis showed that all three types of marine sponges as sources of bacterial isolates had a slimy body surface (Figures 1-3). The mucus on the surface of the sponge body is anticipated to be a substance produced by symbiotic bacteria for self-protection and adaptation to the dynamics in the sponge's growth habitat [5,15,55]. The three types of consortium bacteria (Table 2) reacted positively with several phenotypic test reagents, indicating their specific ability to biodegrade PAHs, such as pyrene and anthracene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the morphological analysis showed that all three types of marine sponges as sources of bacterial isolates had a slimy body surface (Figures 1-3). The mucus on the surface of the sponge body is anticipated to be a substance produced by symbiotic bacteria for self-protection and adaptation to the dynamics in the sponge's growth habitat [5,15,55]. The three types of consortium bacteria (Table 2) reacted positively with several phenotypic test reagents, indicating their specific ability to biodegrade PAHs, such as pyrene and anthracene.…”
Section: Discussionmentioning
confidence: 99%
“…Each compound is characterized by functional groups identified according to the range of wavenumbers. Overall, it can be stated that a longer interaction time led to an increase in the number of components and the types of components (Figure 5A-E), dominated by alcohols, aldehydes, ketones, carboxylic acids, and some aromatic components [5,8,11] cordingly, it can be stated that (1) the number of components resulting from biodegradation tended to increase with increasing interaction time, (2) the types of biodegradation products were different, and (3) all biodegradation products were organic compounds with dominant characteristics in the form of hydroxyl and carbonyl functional groups.…”
Section: Functional Groups Of Biodegradation Productsmentioning
confidence: 91%
See 2 more Smart Citations
“…Bacteria in the marine can form independent communities, generally having specific characteristics and characteristics depending on their habitat [1,[39][40][41]. Bacterial communities living in marine areas are exposed to wastes such as heavy metals, PAHs, pesticides, and biphenyl polychloride [2,42,43]. Those generally have the character and ability to adapt to these contaminants.…”
Section: Introductionmentioning
confidence: 99%